2020
DOI: 10.1016/j.jhepr.2020.100142
|View full text |Cite
|
Sign up to set email alerts
|

Cost of non-alcoholic steatohepatitis in Europe and the USA: The GAIN study

Abstract: There has been little research into the socioeconomic burden associated with non-alcoholic steatohepatitis (NASH). Direct medical, direct non-medical and indirect costs resulting from NASH were captured in a realworld setting. Extrapolating the per-patient cost to a population level demonstrates the rising prevalence of NASH and related comorbidities. Lay summary There has been little research into the socioeconomic burden associated with non-alcoholic steatohepatitis (NASH). The GAIN study provides real-world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
103
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(121 citation statements)
references
References 29 publications
1
103
0
1
Order By: Relevance
“…The mean annual total direct costs for NASH patients in Spain were €3323. [ 44 ] This was relatively lower than the costs reported in this study, which might be attributed to the inclusion of more ill, hospitalized patients as well as those with NAFLD in our study cohort.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The mean annual total direct costs for NASH patients in Spain were €3323. [ 44 ] This was relatively lower than the costs reported in this study, which might be attributed to the inclusion of more ill, hospitalized patients as well as those with NAFLD in our study cohort.…”
Section: Discussionmentioning
confidence: 54%
“…These findings are consistent with previous studies that report a substantial impact of NAFLD/NASH on healthcare resource utilization and costs, particularly for patients with advanced liver diseases. [ 1 , 3 , 5 , 25 27 , 37 , 38 , 42 44 ] Two real-world analyses of administrative databases of Italian local health units and the French hospital system found that more severe liver disease was associated with higher mean total annual costs in hospitalized NAFLD/NASH patients. Inpatient services were the primary driver of higher costs, and costs were generally higher for patients with more advanced liver disease compared to those with less severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…From a public health perspective attention must be paid to NAFLD prevention owing to the substantial health and economic implications of advanced disease, 32 together with the lack of effective pharmacological therapies. NAFLD is closely related to a range of modifiable risk factors linked to the built environment, sociocultural context, and psychological factors.…”
Section: Discussionmentioning
confidence: 99%
“…3 The global prevalence is estimated to be 25% [95% CI: 4 and between 2012 to 2017 the disease was the most rapidly growing contributor to liver mortality and morbidity. 5 With an estimated prevalence of 24% [95% CI: [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Europe has a high burden of NAFLD, 4 which is closely associated with the increasing prevalence of obesity, metabolic syndrome, and type 2 diabetes mellitus (T2DM). 6,7 By 2025, obesity in Europe is forecasted to increase in 44 countries, with 33 of the 53 World Health Organization (WHO) European Region countries estimated to have a prevalence of over 20%.…”
Section: J O U R N a L P R E -P R O O F Introductionmentioning
confidence: 99%
“…O'Hara and colleagues explored the socio-economic burden of NASH in a retrospective, cross-sectional study, in which physicians provided demographic, clinical and economic patient information via an online survey. 2 The Global Assessment of the Impact of NASH (GAIN) determined the mean total annual per patient cost of NASH across major European countries and the United States at €2,763, €4,917 and €5,509 for direct medical, direct non-medical and indirect costs. National per patient cost was highest in the United States and lowest in France.…”
mentioning
confidence: 99%